PENGGUNAAN PERSPEKTIF POSITIVE ACCOUNTING THEORYTERHADAP KONSERVATISMA AKUNTANSIDI INDONESIA - Yevi Dwitayanti Toni Wijaya (JURNAL RISET TERAPAN AKUNTANSI, 2017)
This study aims to analyze the effect of using Positive Accounting Theory Perspective of AccountingConservatism in Indonesia in manufacturing company from 2008 to 2012. Independent variables of this study are Manajerial Ownership, Public Ownership, Leverage, Profitability, and Firm Size. While the dependent variable of this study is Accounting Conservatism. The data which used in this study were obtained from Indonesian Capital Market Directory (ICMD) for 2008 - 2012 period and historical data published by Indonesia Stock Exchange.There is a population of 139 manufacturing companies. The sampling  technique  used  is  purposive  sampling  with  having  sample  criteria  is  manufacturing companies listed on the IDX (Indonesia Stock Exchange)   in the period 2008 to 2012, so will be obtained 35 as a sample of research with 175 observation data. The method of analyzing data used is multiple linear regression analysis with using of SPPS software version 19. The results of this study to indicate that manajerial ownership, leverage and profitabiltas have a significant effect of accounting conservatisma. Public ownership, firm size have no effect of accounting conservatism.